Intravenous Thrombolysis for a Stroke Mimic Patient - Lilly Nguyen (Karger Publishers, 2021)
The authors present the case of a young woman on phentermine and herbal supplements who presented as an acute stroke alert with right-sided facial droop and numbness. She was treated acutely with intravenous tissue plasminogen activator (tPA). However, the workup did not reveal any evidence of cerebrovascular disease or cerebral infarct. The authors discuss plausible stroke mimics and the safety of administering tPA to such patients.